Optimizing PAUD Teacher Creativity Through the 'Loose Parts' Workshop - Rahmawati, Reni; Daryana, Andepi; Hidayat, Paridah (Pasundan Community Service Development, 2023)
This Community Service Activity highlights the importance of enriching children's play experiences with a variety of play tools and materials. This activity aims to change PAUD teachers' views on the tools and play materials available in their environment, which are often considered uninteresting or less educative. Through this workshop, participants are taught about the concept of loose parts and how to design a play environment that stimulates children's development in various aspects. This service activity is important because many PAUD teachers do not make optimal use of the tools and play materials around them. This workshop provides a platform for teachers to improve their understanding and skills in presenting interesting and educational play tools and materials. This activity took place for one day in the STAI SILIWANGI Garut Hall, attended by 100 PAUD teachers. This activity includes delivery of material, individual and group assignments, as well as direct practice. This activity is very relevant to the needs of PAUD children and teachers, especially in providing adequate tools and play materials. The results of this workshop show an increase in participants' insight in understanding the concept of children's play tools and materials, as well as their ability to prepare an attractive play environment and encourage children to play. This activity also resulted in an increase in the presentation of a variety of games and evaluation of children's activities. In conclusion, this workshop was successful in increasing the understanding and skills of PAUD teachers in using tools and play materials available around them. Suggestions for the future include ongoing training and the creation of a loose parts warehouse to exchange tools and materials between teachers.